Integrating intervention for substance use disorder in a healthcare setting: practice and outcomes in New York City STD clinics. (2nd January 2016) - Yu, Jiang; Appel, Phil; Rogers, Meighan; Blank, Susan; Davis, Carrie; Warren, Barbara; Freeman, Anthony; Harris, Brett; Hussain, Shazia
ABSTRACT: Objective : This article reports the integration and outcomes of implementing intervention services for substance use disorder (SUD) in three New York City public sexually transmitted disease (STD) clinics. Methods : The screening, brief intervention, and referral to treatment (SBIRT) service model was implemented in the STD clinics in 2008. A relational database was developed, which included screening results, service dispositions, face-to-face interviews with 6-month follow-ups, and treatment information. Results : From February 2008 to the end of September 2012, 146 657 STD clinic patients 18 years or older were screened for current or past substance use disorders; 15 687 received a brief intervention; 954 received referrals to formal substance abuse treatment; 2082 were referred to substance abuse support services such as Alcoholics Anonymous (AA), and 690 were referred to mental health, social or HIV awareness services. Intervention services delivered through SBIRT resulted in improvements in multiple outcomes at 6 month follow-up. Patients who received interventions had reduced SUD risks, fewer mental health problems, and fewer unprotected sexual contacts. Conclusion : Delivery of SUD services in a public health setting represents a significant policy and practice change and benefits many individuals whose SUDs might otherwise be overlooked. Intervention services for substance use disorder were integrated and highly utilized in the STD setting. Further research needs to focus on the long-term impact of SUD interventions in the STD setting, their cost effectiveness, and the extent they are financially sustainable under the new healthcare law.